2014
DOI: 10.1108/msq-04-2013-0072
|View full text |Cite
|
Sign up to set email alerts
|

The impact of relational bonds on brand loyalty: the mediating effect of brand relationship quality

Abstract: Purpose – While the literature attends to how customer retention strategies develop relationship quality (e.g. trust), it does not account for the potential mediator (s) in this relationship. The purpose of this paper is to examine the mediating role of brand relationship quality (BRQ) in the relationship between relational bonds and brand loyalty in retail service contexts. Design/methodology/approach – A total of 524 valid questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 67 publications
(147 reference statements)
2
43
1
Order By: Relevance
“…With intense competition among global hotel companies, branding strategies has emerged as competitive advantage to increase market share and enhance customer loyalty (Lin, 2013). Branding is considered a power means of the strength of the customer-brand relationship, thus, it is argued that more effort should be placed to improve relationships between customers and the brand as it often lead to a higher intention to repurchase, financial gains, and customer retention (Breivik and Thorbjørnsen, 2008;Huang et al, 2014;Huber et al, 2010;Smit et al, 2007). Brand relationship quality (BRQ) is viewed as an emotional ties resulting from the interaction between the consumer and his/her brand (Fournier, 1998).…”
Section: Brand Relationship Quality (Brq)mentioning
confidence: 99%
“…With intense competition among global hotel companies, branding strategies has emerged as competitive advantage to increase market share and enhance customer loyalty (Lin, 2013). Branding is considered a power means of the strength of the customer-brand relationship, thus, it is argued that more effort should be placed to improve relationships between customers and the brand as it often lead to a higher intention to repurchase, financial gains, and customer retention (Breivik and Thorbjørnsen, 2008;Huang et al, 2014;Huber et al, 2010;Smit et al, 2007). Brand relationship quality (BRQ) is viewed as an emotional ties resulting from the interaction between the consumer and his/her brand (Fournier, 1998).…”
Section: Brand Relationship Quality (Brq)mentioning
confidence: 99%
“…Social bonds are important antecedents of trust in the service encounter (Morgan & Hunt, 1994) and trust is intrinsic in relationship building. Many previous studies highlighted the importance of bonds to overall organisational performance by enhancing customer satisfaction, trust and commitment (Wang et al, 2006;Cater & Cater, 2009;Chen & Chiu, 2009;Fang;Chang & Fang, 2014;Julian et al, 2016). Various literatures suggest the importance of bonds in creating trust in relationships between buyerssellers.…”
Section: Bonds and Relationship Quality: Trust Commitment And Satisfacmentioning
confidence: 99%
“…Previous research has also shown that consumers have an ideal self-image and strive to consume brands that will boost their self-esteem (Carlson et al, 2009). Furthermore, the stronger the link between brand personality and a consumer's self-image, the greater is the likelihood that the consumer will possess a meaningful attitude toward the brand and feel an emotional attachment to it (Bodet and Bernache-Assollant, 2011;Kuenzel and Halliday, 2010;Wu et al, 2012), leading to increased brand loyalty (Cheng et al, 2014;Huang et al, 2014;Malhotra, 1988). Evidence also indicates that brand personality directly influences attitudinal (Buil et al, 2013) and behavioral (Brakus et al, 2009) aspects of loyalty.…”
Section: Effect Of Brand Personality On Customer Loyaltymentioning
confidence: 99%